'The green potion is the virus. The blue one is the corona test. The coloured one makes your wish come true': Irish children's changing perceptions of a scientist as a result of the onset of COVID-19. Issue 2 (3rd April 2021) - Leavy, Aisling; Hourigan, Mairead
ABSTRACT: This study explored the impact of the COVID-19 pandemic on primary school children's perceptions of scientists. Perceptions of scientists were examined using Chambers, D. (1983. "Stereotypic Images of the Scientist: The Draw-a-Scientist Test." Science Education 67 (2): 255–265) 'Draw-A-Scientist Test' (DAST) and involved children ( n  = 104), from senior infants and fourth class, making drawings of scientists. Half the drawings were created in March 2020 one week before school closure due to the COVID-19 pandemic and the remainder in November 2020 when schools reopened. Compared to pre-pandemic drawings, images created during the pandemic revealed more informed understandings of scientists and their work and fewer drawings were classed as 'uncategorised'. However, drawings made during the pandemic revealed more stereotypical perceptions of scientists and their work as indicated by the larger number of stereotypical indicators incorporated into drawings. These increases were statistically significant for younger children. A welcome finding was broader conceptions of the nature of a scientists' work, a shift that appeared to be motivated by the context of the COVID-19 pandemic.